Determination of direction factor, Md for MS1553:2002 wind loading for building structure - Hamizah, Jasmi (2010)
Current records from the Malaysia natural disaster studies show that windstorm -causes damages to building. Even though Malaysia has developed 'own code of -practice on wind loading for building structure to support MalaysianStandard -in 2002, ongoing research is still being carried out to update the data in the codes Currently, in Malaysia is refer to Malaysian Standard, MS 15532002 that do not have -the value -of-direction factor, 'Ma. Most -of'design methods in Malaysia are not considering-the effect of wind direction.. .Significantly; .buil'ding orientation on design stage can reduce the wind load impact. Wind speeds data from eights Meteorological Station over the peninsular Malaysia are used in this study. 'Extreme wind speed are -examined by -statistical 'technique -namely -Gumbel method. The 'extreme wind 'speed -data are considered into Iwo conditions, i) Non-Direction Method,(ii) Directional' Method. By using this method extreme wind can be determined at 8 stations in Peninsular 'Malaysia Which are Kuantan, KuaiaTerengganu, 'Mersing, Senal, Subang, -Bayan -Lepas, 'chuping, and Melaka. -From -the 'result, -the 'direction -factor, NTd station was found and the values are recommending in MS 1553:2002. The results also have shown that, at some direction of extreme wind predicted stronger than non direction method. Furthermore 'these values can give guideline 'to The designer to 'orientate -the -building -in 'facing 'high 'wind -speed. It is also -can 'reduce 'factor failure due 10 the extreme wind in Malaysia.